Developing a Paradigm Model for Resilience of Rural Entrepreneurial Businesses in Dealing With the COVID-19 Crisis; Application of Grounded Theory in Western of Iran - Mohammadifar, Yousef; Naderi, Nader; Khosravi, Ehsan; Karamian, Faranak (Frontiers in Public Health, 2022)
Pandemic the COVID-19 is a global threat to rural entrepreneurial businesses with an uncertain ending. Therefore, it is necessary to provide a paradigm model to reduce the negative effects of this crisis, increase the resilience of rural entrepreneurial businesses or even turn this threat into an opportunity for the development of rural entrepreneurial businesses in the long run. This study, using a qualitative approach, investigated the resilience of rural entrepreneurial businesses in dealing with the COVID-19 crisis in Kermanshah province using a paradigm model. Using purposeful and theoretical sampling, 26 cases were selected. The tools used for data collection were open questionnaires (unstructured), individual depth interviews, and taking notes. The results provide a relatively comprehensive model that consists of six basic parts: causal conditions (included economic management, health factors, human resources management, and adaptation factors), the phenomenon (included low resilience of rural entrepreneurial businesses in the face of the Covid-19 crisis), contextual conditions (including social factors; cultural factors and psychological factors), interventing conditions (included business management and legal supports), action strategies (included Planned resilient actions and Unplanned resilient actions), finally, the consequences (included adapting to crisis conditions and increasing resilience in the long run, and also lack of adaptation to crisis conditions and lack of continuity of business survival in the long run). In general, rural entrepreneurial businesses in the face of crisis must, through planned resilience measures, both increase their business resilience in the short term, as well as develop the business and gain a competitive advantage in the long run. Finally, based on the findings and in order to developing resilience in rural entrepreneurial businesses during the COVID-19 crisis, some recommendations were presented.